Compatibility of pTM89, a new F-like R factor, and of derivative plasmids. - Monti-Bragadin, C (1975)
pTM89, an fi+ R factor that controls the production of repressed F-type pili, is incompatible with plasmids belonging to the FII and P groups. The results of P1 transduction show that all of the resistance markers of pTM89 are part of a single replicon, which also includes RTF. When the compatibility of different derivative plasmids was investigated, it was found that they fall into two classes. Those of the first class have lost the compatibility of pTM89 for the P group but are still incompatible with FII group, whereas those of the second class are compatible with plasmids of both groups. Plasmids of the latter class that are also compatible with each other and, therefore, apparently lack any determinant for compatibility are genetically stable and self-transmissible. It appears, therefore, that compatibility between plasmids cannot be explained by the hypothesis of competition for a maintenance site.